2023
DOI: 10.3390/diagnostics13101751
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Dual-Energy CT Material Decomposition Technique for Assessing Bone Status Compared with Quantitative Computed Tomography

Abstract: Purpose: The purpose of this study was to evaluate the diagnostic accuracy when using various base material pairs (BMPs) in dual-energy computed tomography (DECT), and to establish corresponding diagnostic standards for assessing bone status through comparison with quantitative computed tomography (QCT). Methods: This prospective study enrolled a total of 469 patients who underwent both non-enhanced chest CT scans under conventional kVp and abdominal DECT. The bone densities of hydroxyapatite (water), hydroxya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…For instance, the existence of bone marrow adipose tissue leads to an underestimation of spine BMD, and this error will amplify with higher fat content ( 25 ). A similar finding was also reported in another DECT study in which the utilization of substance decomposition method (fat vs. HAP) for diagnosing osteoporosis yielded unsatisfactory results, with an AUC of only 0.594 ( 26 ).…”
Section: Discussionsupporting
confidence: 85%
“…For instance, the existence of bone marrow adipose tissue leads to an underestimation of spine BMD, and this error will amplify with higher fat content ( 25 ). A similar finding was also reported in another DECT study in which the utilization of substance decomposition method (fat vs. HAP) for diagnosing osteoporosis yielded unsatisfactory results, with an AUC of only 0.594 ( 26 ).…”
Section: Discussionsupporting
confidence: 85%
“…Yue et al reported that using calcium and water as base materials could reflect the age-related changes in the lumbar spine of adult women and its correlation with BMD [19]. Wang et al proved that measurement using the hydroxyapatitewater base material pair provides high diagnostic accuracy [20].…”
Section: Introductionmentioning
confidence: 99%